Review of opportunities for the Pacific WASH sector
The report provides an overview of the WASH sector in Pacific island countries in the context of the coronavirus disease (COVID-19) pandemic. It highlights the urgency of strategic WASH interventions and provides recommendations for the Asian Development Bank and its partners. It highlights opportunities to (i) promote more investment in the sector, (ii) strengthen the capacity of WASH providers to improve access to and quality of services, and (iii) address WASH for health more comprehensively through coordinated approaches.